Progress in the development of table-top discharge-pumped soft x-ray lasers - Macchietto, C. D., author; Chilla, J. L. A., author; Gonzalez, J. J., author; Benware, B. R., author; Marconi, M. C., author; Shlyaptsev, V. N., author; Moreno, C. H., author; Tomasel, F. G., author; Rocca, Jorge J., author; [EDP Sciences], publisher (Colorado State University. Libraries, 1997)
The demonstration of large soft x-ray amplification in a discharge-created plasma has opened a new path to the development of compact and practical soft x-ray lasers. We review our progress in the development and study of these ultrashort wavelength lasers. The field has advanced from the first observation of large amplification in a discharge-created plasma in Ne-like Ar, to the demonstration of an extremely compact saturated laser at 46.9 nm. In this paper we give overview of these and other selected results. They include the observation of large amplification (gain-length product of 7 .5) in Ne-like S at 60.8 nm in material ablated from a solid target by a discharge, and preliminary results of the search for gain at a shorter wavelength in Ne-like Ca. A recent study of the spatial coherence of the capillary discharge 46.9 nm Ne-like Ar laser, which provides the first experimental measurement of a monotonic increase of the spatial coherence with length in a soft x-ray amplifier, is also summarized.